Peran Kepala Sekolah dalam memanajerial kurikulum di Madrasah Tsanawiyah (MTS) Samailul Huda, Demak - As'ad; Fatimah (Lancar Media Komunikasi, 2023)
The purpose of this study was to analyze the role of the school principal in managing the curriculum at Samilul Huda Madrasah (MTs) Mlaten Village, Mijen District, Demak Regency. This research uses a qualitative approach and the method used is a case study which aims to photograph events, facts, data, and incidents regarding curriculum management at the school. Sources of data from this study were the principal as the key informant (main source) and all MTs Samal Huda teachers. The techniques and procedures for data collection were carried out by means of in-depth interviews, observations or observations of researchers in field activities, and analysis of documents related to the object of this research. The results of the study can be concluded that there are three roles that are quite effective for the principal in managing the curriculum (1) planning consisting of technical and teacher understanding, (2) implementing the curriculum in class learning (3) and evaluating learning outcomes and class learning.Keywords: curriculum, planning, implementation, evaluation.